Pengaruh Keaktifan Siswa dalam Mengikuti Program Gabungan Remaja Islam terhadap Komitmen Beragama Islam - Yenifa Nur Annisa Yenifa; Eko Surbiantoro Eko; Huriah Rachmah (Bandung Conference Series: Islamic Education, 2023)
Abstract. Islamic Senior High School (ISHS) 1 Bandung City has an unresolved problem, namely the existence of juvenile delinquency who are members of the student community. On the other hand, the school has Islamic spiritual extracurricular activities which are superior in terms of the moral development of its members. Based on these problems, the formulation of the problem posed is: "How much influence does student activeness in participating in the Islamic youth association program have on Islamic religious commitment at ISHS 1 Bandung City". The theory of liveliness uses the theory from Sriyono while the theory of Islamic religious commitment from Glock and Stark which is modified by Agus Sofiyandi Kahfi. Based on the theoretical approach, the hypothesis formulated is: "There is a significant influence between student activity in participating in the combined program of Muslim youth on Islamic religious commitment at ISHS 1 Bandung City". The research approach uses a quantitative approach. The population of this study were students who were members of the combined Islamic youth during the 2022/2023 jihad, totaling 80 members. Because the total population is less than 100, the entire population is used as a sample of all elements. The data source for this research is a questionnaire. The analysis technique used is simple linear regression analysis. This technique is to find out how much influence student activity in the combined Islamic youth program has on Islamic religious commitment. The results showed that there was a significant influence of 0.599 (59.9%) between students' activeness in participating in the combined program of Islamic youth on Islamic religious commitment at ISHS 1 Bandung City. So, the hypothesis put forward is that the activeness of students participating in the combined program of Islamic youth towards Islamic religious commitment at ISHS 1 Bandung City has a significant effect and has been tested empirically. Abstrak. MAN 1 Kota Bandung memiliki permasalahan yang belum terselesaikan yaitu terdapat kenakalan remaja yang tergabung dalam komunitas pelajar. Disisi lain, sekolah mempunyai kegiatan ekstrakulikuler kerohanian Islam yang unggul dalam segi pembinaan akhlak anggotanya. Berdasarkan permasalahan tersebut, rumusan masalah yang diajukan adalah: “Seberapa besar pengaruh keaktifan siswa dalam mengikuti program gabungan remaja Islam terhadap komitmen beragama Islam di MAN 1 Kota Bandung”. Teori keaktifan siswa menggunakan teori dari Sriyono sedangkan teori komitmen beragama Islam dari Glock dan Stark yang dimodifikasi oleh Agus Sofiyandi Kahfi. Berdasarkan pendekatan teori, hipotesis yang dirumuskan adalah: “Terdapat pengaruh yang signifikan antara keaktifan siswa dalam mengikuti program gabungan remaja Islam terhadap komitmen beragama Islam di MAN 1 Kota Bandung”. Pendekatan penelitian menggunakan pendekatan kuantitatif. Populasi penelitian ini adalah siswa yang menjadi anggota gabungan remaja Islam masa jihad 2022/2023 berjumlah 80 anggota. Karena jumlah populasi kurang dari 100, maka seluruh populasi dijadikan unsur sampel seluruhnya. Sumber data penelitian ini berupa angket. Teknik analisis yang digunakan adalah analisis regresi linear sederhana. Teknik tersebut untuk mengetahui seberapa besar pengaruh keaktifan siswa dalam program gabungan remaja Islam terhadap komitmen beragama Islam. Hasil penelitian menunjukan adanya pengaruh yang signifikan sebesar 0,599 (59,9%) antara keaktifan siswa dalam mengikuti program gabungan remaja Islam terhadap komitmen beragama Islam di MAN 1 Kota Bandung. Maka, hipotesis yang diajukan yaitu Keaktifan siswa mengikuti program gabungan remaja Islam terhadap komitmen beragama Islam di MAN 1 Kota Bandung berpengaruh secara signifikan dan teruji secara empirik.